Edukasi Pendidikan Karakter, Nilai dan Implementasi untuk Siswa di SMP PGRI Pekanbaru - Ferazona, Sepita; Suryanti; Kalsum, Ummi; Hadiyanti, Putri Octa; Mellisa, Mellisa; Fauziah, Nurul; Putri, Iffa Ichwani; Santika, Rosi; Herlini, Fira (Community Education Engagement Journal, 2025)
Students who participate in community service projects are expected to develop moral character in addition to scholastic aptitude. Instilling moral principles that can mold pupils' personalities and characters and be used in everyday situations is the major objective. by spreading awareness of the value of developing moral character in day-to-day interactions. The development of morally and ethically sound attitudes and behaviors, such as honesty, accountability, discipline, empathy, and teamwork, is the main goal of character education. These principles serve as the cornerstone for developing people who possess both high moral standards and intellectual prowess. Character education can be implemented in a number of ways, including by incorporating character values into the curriculum, extracurricular activities, and community-based social learning activities like parent-teacher training or mutual cooperation. In order to create better, more responsible people, it is intended that SMP PGRI Pekanbaru students will be better able to comprehend and practice character education. According to the findings of the conducted interviews, the school has responded well to the service projects that have been carried out.